Discourse coherence and VP ellipsis with split antecedents - Baker, Adam C. (Proceedings of the Amsterdam Colloquium, 2007)
Pr¨üst et al. 1994 propose a model of discourse coherence that resolves VP ellipsis reference as a side effect of coherence establishment. This paper extends that framework using the Cause-Effect model from Kehler 2002. The extended framework allows a straightforward account of split antecedent cases of VP ellipsis from Webber 1978.